Impacto da hipertrofia mamária e da mamoplastia redutora na imagem corporal - Fonseca, Cristiane Costa [UNIFESP] (2017)
Introduction: Body image dissatisfaction is the main component that motivates the seek for plastic surgery; however, there are few studies that associate it with reduction mammaplasty. Objective: To evaluate the impact of breast hypertrophy and breast reduction on women´s body image. Methods: Women with breast hypertrophy scheduled for breast reduction from June 2013 to December 2015 were prospectively evaluated (mammaplasty group), as well as women with normal sized breasts (normal size breast group). The Body Dysmorfic Disorder Examination (BDDE), the Body Investment Scale (BIS) and the Breast Evaluation Questionnaire (BEQ55) were applied by interview at baseline and after six months. For the analysis it was applied ANOVA with repeated measures, for intergroup and intragroup comparisons between time points. Results: A total of 103 women in each group were enrolled. In the intergroup comparison, after the operation, women who underwent mammaplasty presented less negative body image symptoms (BDDE, p≤0.001) and were more satisfied with the body and breasts (BIS, p=0.157) than normal volume breasts women, besides to invest more in appearance (BEQ55, p≤0.001). Conclusion: The reduction mammaplasty improved body image of women with breast hypertrophy.